2022
DOI: 10.1093/brain/awac129
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from aphasia in the first year after stroke

Abstract: Most individuals who experience aphasia after a stroke recover to some extent, with the majority of gains taking place in the first year. The nature and timecourse of this recovery process is only partially understood, especially its dependence on lesion location and extent, which are the most important determinants of outcome. The aim of this study was to provide a comprehensive description of patterns of recovery from aphasia in the first year after stroke. We recruited 334 patients with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 97 publications
0
36
0
Order By: Relevance
“…Overall, the results demonstrate that blood flow is reduced beyond the lesion site in chronic post-stroke aphasia and hypoperfused neural tissue in critical temporo-parietal language areas may not be fully able to support recovery. The findings underscore the critical and general role that left hemisphere posterior temporal regions play in various expressive and receptive language abilities (Ivanova et al, 2016; Ivanova, Zhong, Turken, Baldo, & Dronkers, 2021; Turken & Dronkers, 2011; Wilson et al, 2022). Overall, the study shows that slowed or reduced blood distribution can affect the functionality of regions beyond the lesion site and have a direct impact on behavioral outcomes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Overall, the results demonstrate that blood flow is reduced beyond the lesion site in chronic post-stroke aphasia and hypoperfused neural tissue in critical temporo-parietal language areas may not be fully able to support recovery. The findings underscore the critical and general role that left hemisphere posterior temporal regions play in various expressive and receptive language abilities (Ivanova et al, 2016; Ivanova, Zhong, Turken, Baldo, & Dronkers, 2021; Turken & Dronkers, 2011; Wilson et al, 2022). Overall, the study shows that slowed or reduced blood distribution can affect the functionality of regions beyond the lesion site and have a direct impact on behavioral outcomes.…”
Section: Discussionmentioning
confidence: 65%
“…The findings underscore the critical and general role that left hemisphere posterior temporal regions play in various expressive and receptive language abilities. 49,5355 Overall, the study shows that slowed or reduced blood distribution can affect the functionality of regions beyond the lesion site and have a direct impact on behavioral outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…Due to the relatively small sample size, we were not able to study different patient subgroups separately. Although the covariate “old lesion load” (including old stroke lesion load) did not significantly contribute to any of the regression models, future (larger-scale) independent studies are crucial to validate our findings ( Poldrack et al, 2020 ) and could check whether the found effects hold or differ in various subgroups of patients ( Wilson et al, 2022 ), such as patients with and without stroke history, patients with different stroke types or language lateralization patterns.…”
Section: Discussionmentioning
confidence: 71%
“…The response to phrase-structure building demands (evidenced by a stronger response during sentence production than word-list production) was reliable in every language fROI. This distributed nature of phrase-structure building a) parallels the distributed effects of syntactic demands during language comprehension (e.g., Blank et al, 2016; Shain, Blank et al, 2020; Shain et al, in press), and b) aligns with evidence from aphasia, where damage to both frontal and temporal language areas and the white matter tracts connecting them can result in syntactic deficits (e.g., Kempler et al, 1991; Caplan et al, 1996; Dick et al, 2001; Wilson & Saygin, 2004; Mesulam et al, 2015; Wilson et al, 2022; see deBleser, 1987 for a discussion of earlier evidence), thus adding to the growing evidence against focal implementation of combinatorial linguistic processing. Importantly, we showed that the sentence > word-list effect in production cannot be explained by general cognitive demands.…”
Section: Discussionmentioning
confidence: 73%